Does Kidney Transplantation Affect Sleep and Fatigue in Patients With Kidney Disease?. Issue 6 (June 2019) - Tandukar, Srijan; Hou, Surui; Yabes, Jonathan; Ran, Xinhui; Fletcher, Mary; Strollo, Patrick; Patel, Sanjay R.; Unruh, Mark; Jhamb, Manisha
Abstract : Background: Sleep disorders and fatigue are highly prevalent in chronic kidney disease (CKD) and end-stage kidney disease (ESKD) patients but there is limited evidence on the effect of kidney transplant (KTx) on these. Methods: In a prospective cohort study of patients with advanced CKD (estimated glomerular filtration rate<30 mL/min/1.73 m 2 ) or ESKD, polysomnography and patient-reported symptom assessments were conducted. Pre- and post-KTx changes in sleep apnea (SA) severity (measured by apnea hypopnea index [AHI]) were analyzed and compared with patients who did not receive KTx. Regression models were used to examine predictors of SA severity. Results: Among 77 patients (mean age 51 y, BMI 29 kg/m 2, 66% males, 23% ESKD), 61% had SA at baseline. Among 39 KTx recipients, 56% had SA, with 39% having moderate-severe SA after 10 ± 5.6 months post-KTx. There was no difference in AHI in either the KTx (median 6 versus 8; P = 0.37) or no-KTx (median 15 versus 16; P = 0.61) groups after an average of 19.9 ± 8.9 months. KTx led to significant clinically meaningful improvements in fatigue and health-related quality of life (adjusted effect size 0.3–0.6). In multivariable regression, baseline AHI was the only significant predictor of SA severity (adjusted β = 3.6/5 units, 95% confidence interval 2.1, 5.2) after adjusting for KTx status, age, sex, and body mass index. Conclusions: More than half of the KTx recipients had SA. There was no significant change in SA severity with KTx. Clinically meaningful moderate size improvements in patient-reported fatigue and health-related quality of life may be seen with KTx. Abstract : Supplemental Digital Content is available in the text.